Răspunsuri

Cel mai inteligent răspuns!
2014-11-13T22:26:02+02:00
{2⁵+5X[3²-(3X-2)·2+5²]-2³·3²}·7+60=900
{2⁵+5·[9-6X+4+25]-8·9}·7=900-60
{32+5·[38-6X]-72}·7=840
32+5(38-6X)-72=840:7
32+190-30X-72=120
150-30X=120
30(5-X)=120
5-X=120/30
5-X=4
-X=4-5
-X=-1   (-1)
X=1


2014-11-13T22:32:21+02:00
 { 2^{5} +5x [ 3^{2} -(3x-2)*2+ 5^{2} ]- 2^{3} * 3^{2} }*7+60=900
{32+5x[9-(3x-2)*2+25]-8*9}*7+60=900
{32+5x[9-6x-4+25]-72}*7+60=900
{32+45x-30x^2-20x+125x}*7+60=900
224+315x-210x^2+875x+60=900
-210x^2+1190+284=900
-210x^2=-574 inmultim prin -1
210x^2=574
x=1.65